(untitled) (Mustansiria Dental Journal, 2018)
This study was conducted to establish the prevalence of different reactive hyperplastic lesions of the gingiva in a university-based dental school biopsy service. Biopsy records over a 12-years period (1982-1994) were retrieved from the files of the department of Oral Pathology, College of Dentistry, University of Baghdad. The lesions were reclassified into: Fibrous lesions (like Focal Fibrous Hyperplasia FFH and Ossifying Fibrous Epulis OFE); vascular lesions (like Pyogenic granuloma) and Giant cell lesions (like Peripheral giant cell granuloma PGCG). The available clinical data regarding age, gender and location were obtained for each case. The majority of lesions were pyogenic granuloma which constituted 49.2% with female predilection. Peoples in the first and second decade of life were more prone to develop gingival lesions especially in upper anterior region. This study indicates some differences in age and gender distribution as well as in location between the different lesions.